Complete chloroplast genome sequences of six lines of Echinochloa colona (L.) link - Hereward, James P. (Mitochondrial DNA B Resour, 2017)
Barnyard grass (Echinochloa colona, (L.) Link) is the wild relative of barnyard millet (E. frumentacea (Roxb.) Link). This species, widely distributed globally, is an agricultural weed and has developed resistance to several herbicides including glyphosate. This paper presents the complete chloroplast sequences of two haplotypes (139,718 bp & 139,719 bp) sequenced from six lines of E. colona from Australia. The E. colona chloroplast sequence is very similar to that of E. frumentacea (163–169bp =0.12% differences across the genome). The gene content, arrangement, and the inverted repeat structure is the same as in the other species of Echinochloa sequenced to date.